Subclinical depression and anxiety as an additional risk factor for cardiovascular events in low- and moderate-risk patients: data from 10-year follow-up - M. D. Smirnova; O. N. Svirida; T. V. Fofanova; Z. N. Blankova; E. B. Yarovaya; F. T. Ageev; S. A. Boytsov (Кардиоваскулярная терапия и профилактика, 2021)
Aim. To assess the contribution of anxiety (A) and depression (D) to the increased risk of cardiovascular events (CVEs) in patients with Systematic Coronary Risk Evaluation (SCORE) <5% according to 10-year follow-up.Material and methods. The work included 190 patients with SCORErisk <5%, examined in 2009-2010. In addition to the standard examination, a questionnaire was carried out using Hospital Anxiety and Depression Scale (HADS). In 2019, we contacted participants by telephone to identify CVEs over the past time: death from cardiovascular diseases (CVDs), acute myocardial infarction (MI), unstable angina, stroke, revascularization. The response was 86,3%.Results. CVEs occurred in 17 (10,2%) patients and included following outcomes: 3 deaths from CVDs, 6 acute MIs, 4 cases of unstable angina, 12 revascularizations. Patients with and without CVEs differed only in the depression level — 7 (5; 7) vs 5.0 (4; 5) points (p=0,0001). HADS-D score >6 increased the probability of CVEs — odds ratio (OR) 2,9 (1,1-7,7). In individuals with HADS-D score >6 and/or HADS-A score >7, the probability of CVEs increased — OR 4,9 (1,4-17,9). A combination of impaired two or more parameters of the lipid profile, systolic blood pressure >130 mm Hg and HADS-D score >6 and/or HADS-A score >7 increased the risk of CVE — OR 7,3 (2,48-21,36).Conclusion. Depression, including subclinical depression, is associated with an increased risk of CVEs in patients with a SCORE risk <5%.